Wavell : Soldier & Statesman - Schofield, Victoria (Karachi Oxford University Press, 2017)
Originally published: London: John Murray, 2006
Include Map, Notes, Illustration, Bibliography and Index
Keywords: Statesmen -- World War (1939-1945) -- Military campaigns